Method for Choosing a Balanced Set of Fault-Tolerance Techniques for Distributed Computer Systems - Volkanov, D. Yu (Automatic control and computer sciences, 2017)
We consider the problem of choosing a balanced set of fault-tolerance techniques for distributed computer systems. In this problem, it is necessary to choose a balanced set of versions of the modules of distributed computer systems, during which the reliability of the set must be maximized under cost constraints (on the set of possible versions of distributed computer systems). We describe the fault-tolerance techniques out of which the choice is made and consider a mathematical model in the context of which the formulation of the problem and the method of its solution are given. This problem is widely considered in the literature. A detailed description of the method for choosing a balanced set of fault-tolerance techniques for distributed computer systems is presented. The proposed method represents an evolutionary algorithm using the scheme of fuzzy logic. The scheme of fuzzy logic in the process of operating the algorithm analyzes the results of its operation in each generation and from this information adjusts the parameters of the evolutionary algorithm. The method makes it possible to obtain an efficient solution, as shown in the experimental research. A key feature of the proposed approach is the use of an adaptive scheme. The method has been implemented as software integrated with the DYANA simulation environment. The conclusions of the paper contain a brief description of future research directions.